Efforts to Increase the Use of Indonesian for Class XII at SMK Karya Bahana Mandiri, East Bekasi - Farisha Hana; Anis Dwi Winarsih (Universitas Merdeka Malang, 2023)
The widespread use of slang in the younger generation threatens the existence of Indonesian. In fact, many young people have lost their pride in using Indonesian. They are more proud to use English, even slang because it is considered prestige. Based on this, the use of Indonesian needs to be improved. This research was conducted at Karya Bahana Vocational School in Class XII in the Indonesian language subject, with an emphasis on students' speaking skills when presenting the text of the observation report. The method used is a collaborative method based on classroom action research, which consists of planning, implementing, observing, and reflecting. The aspects of assessing speaking skills which are indicators of the use of Indonesian in SMK Karya Bahana are aspects of word choice, voice intonation, facial expressions, and gestures during presentations. The results of the research obtained are that the use of Indonesian at SMK Karya Bahana has increased, from the four aspects of the assessment.